SPIRONOLACTONE IN FIRST-LINE ANTIHYPERTENSIVE THERAPY: EFFECT ON VASCULAR REMODELING - Anna Mikhailovna Torunova (Байкальский медицинский журнал, 2023)
Introduction. Previously, clinical studies have proven a pronounced antihypertensive effect of spironolactone in patients with true resistant hypertension. The effectiveness of spironolactone as part of first-line therapy, as well as the effect on vascular wall remodeling, has not been studied.Target. To study the effect of spiroconolactone as part of the first line of therapy when added to telmisartan on indicators of vascular wall stiffness in patients with hypertension at high/very high cardiovascular risk.Materials and methods 32 patients (54 (45; 59) years old) were randomly divided into two groups: in the main group receiving spironolactone at a dose of 25 mg in addition to telmisartan (ARB/spironolactone) and in the group receiving hydrochlorothiazide/ARB combination (control). group).Inclusion criteria: age of patients (30-65 years), hypertension at high/very high cardiovascular risk without antihypertensive therapy, no contraindications to prescribed drugs. At baseline and 6 months later, all patients underwent clinical (office) blood pressure (BP) measurements, ABPM, endothelium-dependent vasodilation (EDVD), vascular remodeling indicators: central blood pressure (CAP), augmentation index, pulse wave velocity (PWV). In patients in the ARB/spironolactone group, serum potassium levels were assessed at baseline and after 4 weeks of treatment.Results. In both groups, a significant decrease in clinical and average daily blood pressure was revealed, as well as a decrease in the augmentation index and CAP. PWV in the carotid-radial segment (CWCR) did not significantly decrease in both groups, while PWV in the carotid-femoral area (CWCF) decreased in the ARB/spironolactone group from 9.8 (9.0; 10.6) m/s to 8.6 (8.0; 10.2) m/s (p = 0.0007). The dynamics of SPWcr was 0.9 (1.3;-0.5) m/s in the ARB/HCT group. In all patients, blood potassium was within reference values.Conclusions. Spironolactone as part of first-line therapy, when added to ARBs in patients with hypertension at high/very high cardiovascular risk, led to a significant decrease in clinical and mean daily blood pressure, as well as a decrease in PWCF.